DYNAMIC FILTERING METHODS IN INFORMATION COMMUNICATION SYSTEMS - Raxmanqulova Mashhura Ruziboyevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation. In the context of Information Communication Systems (ICS), dynamic filtering rules represent a flexible and flexible approach to filtering incoming and outgoing data. In this article, you can get answers to questions about dynamic filtering methods, their configuration and development, the main features of dynamic filtering rules, what role dynamic filtering plays as an important protector of efficiency and security. Information has also been cited on current examples of dynamic filtering